Herpetofaunal Assemblages in the Lowland Regions of Sumatera Barat - Fitra Arya Dwi Nugraha; Fajar Kaprawi; Rijal Satria; Ahmad Muammar Kadafi; Ade Prasetyo Agung (Universitas Gadjah Mada, 2022)
The habitat destruction and land-use changes caused the decline of animal composition in many tropical regions. Here, we study the diversity of herpetofauna in the lowland areas in Sumatera Barat, a midwestern province in Sumatera island, using a visual encounter survey method. The surveyed habitat included rubber plantations, streams, paddy fields, and peat swamps. We observed 338 individuals representing 44 species from 14 families of herpetofauna with almost 90% individuals were amphibians. Overall, the rubber plantations contained a higher number of species than other types of habitat. For amphibians, Ranidae and Dicroglossidae represented the first and the second highest both in the species and individual number. For reptiles, Agamidae and Colubridae or Gekkonidae accounted for the first and the second highest in the individual number while Colubridae and Scincidae consisted of the highest species number. Our data showed that the diversity index was mostly in moderate level except in paddy field. The species composition in rubber plantations were more similar to those of streams rather than paddy field or peat swamp Sago habitat.